THE PARENTAL GUIDANCE ANALYSIS IN INCREASING STUDENT ACHIEVEMENT ACADEMIC CLASS VI SDN 38 MATARAM ACADEMIC YEAR 2020 (Indonesian Publication Center, 2020)
This research aims to identify parental guidance in improving learning achievement. This research is a descriptive study with a qualitative approach. The subjects in this research were parents of students and students of class VI SDN38 Mataram. Data collection techniques using interview and documentation techniques. This data analysis uses interactive analysis method. The results of the study are the role of parents guiding their children in improving learning achievement is still not optimal. Parents of students still do not pay attention to their children's learning at home, parents also do not overly regulate their children's learning time, then in doing homework parents do not often accompany their children. Parents only accompany, accompany when there are lessons that are not understood that asked their children. Parents of students are also less strict in telling and forbidding for example in instructing to study, forbid playing Cellphone and watching Television so that the child is indifferent in carrying out orders and prohibits. Then the perceived obstacle of parents in guiding their children is CellPhone and Television.